Linking place preference with satisfaction: an examination of its relationship from Tahfiz students perspective - Ab Jalil, Nurlelawati; Zainudin, Farah Eleena; Salleh, Nurul Hamiruddin; Awang, Arita Hanim; Ab. Jalil, Habibah; Salim, Siti Suria (The Mattingley Publishing Co., Inc., 2020)
This paper explored the pattern of students’ learning setting preferences in Al Quran memorisation and satisfaction towards the settings in 10 consecutive days of an experiment. Subjects were assigned to five different Hafazan settings in their learning ecology set based on the findings from the literature. Eight indicators encompass the memorisation performance, comfort level towards setting arrangement and position, perceived wall finishes, furniture ergonomic, brightness level, temperature and privacy, were adapted to record their learning experience in manipulated settings. The objective of this investigation is to study the satisfaction and comfort level of students during Quran memorisation as well as to identify the preferences setting arrangement while memorising the given verses of Quran. The result is segregated between gender. It is pertinent to note, both genders prefer at seat at window face setting. However, male students would rather sit on the chair with a table provided while female students tend to choose sitting with cross-legged. In conclusion, both objectives are achieved. It seems both genders have different preferences in terms of position. The findings are significant for further investigation of Islamic learning ecology and behavioural studies, that is limitedly available for references. Implications of the findings discussed.